MRI predictors for the conversion from contrast-enhancing to iron rim multiple sclerosis lesions: original communication - Wenzel, Nicolas; Wittayer, Matthias Sebastian; Weber, Claudia Ellen; Schirmer, Lucas; Platten, Michael; Gass, Achim; Eisele, Philipp (Journal of neurology, 2022)
In multiple sclerosis (MS), iron rim lesions (IRLs) are characterized by progressive tissue matrix damage. Therefore, early identification could represent an interesting target for therapeutic intervention to minimize evolving tissue damage. The aim of this study was to identify magnetic resonance imaging (MRI) parameters predicting the conversion from contrast-enhancing to IRLs.